Two further Neocaeculus species (Acari: Prostigmata: Caeculidae) from Barrow Island, Western Australia - Taylor, Christopher (Universite de Montpellier III (Paul Valery), 2014)
Two new species of Neocaeculus (Acari: Caeculidae) are described from Barrow Island, Western Australia: Neocaeculus kinnearae and N. nudonates. Neocaeculus kinnearae is a likely epigean species closely related to N. knoepffleri; N. nudonates is likely to be a sand-burrowing species. Neocaeculus knoepffleri and N. bornemisszai are also recorded from Barrow Island.